Antisolvent Crystallization (ASC) in Aqueous System: Fundamentals, Sustainability Aspects, and Applications - Bhatti, Sameer; Sahu, Parul (Journal of Chemical Engineering Research Updates, 2024)
The present perspective focuses on fundamental and applied attributes of antisolvent crystallization (ASC) in aqueous systems and establishes its potential for various industrial applications. In the ASC method, supersaturation is attained by adding a secondary solvent (antisolvent) to a solution leading to the crystallization of the solute. ASC offers the advantages of increasing yields, and conserving energy over the conventional evaporative or cooling crystallization, and thus appears to be a growing industrially important and sustainable process. The insights on the role of phase equilibrium thermodynamics and kinetics in controlling the crystallization process and crystal properties during ASC are discussed. The choice of solvents is a critical factor in ASC, and the solvent type, properties, and selection are considered briefly. The evaluation of the sustainability aspect of ASC by assessing the environmental benignity of solvents, the impact of their life cycles on the ecology, and associated economic costs are presented. A comprehensive list of solvents used for ASC and their usage pattern is also included. Successively reintegrating ASC into process design and developing different process configurations (stand-alone and hybrid) are reviewed. Finally, the paper highlights the opportunity for more widespread application of ASC in the fields of salt extraction, water treatment, hydrometallurgy, bioprocessing, and the pharmaceutical industry.